Derivation of MUAC cut-off to identify undernourished 1-6 months old infants - D., Ramamani; E., Suganya (International Journal of Contemporary Pediatrics, 2018)
Background: Under nutrition is the major public health problem in our country. There are numerous anthropometric methods, one of which is mid upper arm circumference (MUAC). MUAC cut-off classify the nutritional status of the children aged between 6-60 months. However, there is no specific cut-off for MUAC to identify the undernourished infants aged between 1-6 months. With the above background study was planned with the following objectives. Objectives of this study were to classify the nutritional status of 1-6 months aged infants using WLZ classification and to derive a cut off value for Mid upper arm circumference, to define under nutrition/wasting among 1-6 months aged infants Methods: The cross-sectional study was carried out among 706 infants aged between 1-6 months. Nutritional status was assessed using WLZ. Various MUAC was tested against WLZ of <-2, in order to identify the cut-off below which, the infant will be considered undernourished. Results: Mean age of the participants was 96±55 days. Mean weight, length and mid upper arm circumference was 4.75±1.02 kg, 58.51±4.47 cm and 12.15±3.01cm respectively. MUAC cut-off <13.5 cm has yielded highest youden index, accuracy and sensitivity of 0.36, 0.79,99% respectively. The total area under ROC curve is 0.707 [95% CI: 0.66, 0.74; p<0.0001], having a good diagnostic accuracy and it is statistically significant. Conclusions: A MUAC cut-off value below 13.5 cm, among 1-6 months aged infants will be considered to be undernourished.